Youth attitudes towards clerics in Iraq: Anthropological study - Mansoor , Jameel Mohsin (International Journal of Psychosocial Rehabilitation, 2020)
The study is an attempt to shed light on the attitudes of young people towards the clerics in Iraq after 2003, due to their important and direct impact on the political and social processes. After 2003, the environment has created a sort of inclinations and tendencies by individuals. Therefore, being acquainted with these inclinations has necessity to identify the acceptability of religious clerics among young people.